2016
DOI: 10.3109/0886022x.2016.1165065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium channels blockers and inhibitors of the renin-angiotensin system on renal outcomes and mortality in patients suffering from chronic kidney disease: systematic review and meta-analysis

Abstract: (2016) Effect of calcium channels blockers and inhibitors of the renin-angiotensin system on renal outcomes and mortality in patients suffering from chronic kidney disease: systematic review and meta-analysis, Renal Failure, 38:6,[849][850][851][852][853][854][855][856] Background:The renoprotective effect of inhibitors of renin-angiotensin system (RAS) has been identified through placebo-controlled trials. However, the effect of calcium-channel blockers (CCBs) on renal system is still controversial. Our cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…Another hypothesis is that the greater use of calcium channel blockers by hypertensive patients with MetS could have resulted in BP control, but not in avoiding early renal damage, in agreement with several studies. 17 Another point to be mentioned is that despite of the greater use of antidiabetic drugs by patients with MetS, HbA1c remained higher in this group. On the other hand, studies 18 have consistently shown that levels of HbA1c < 7% are associated with a reduced risk of structural and clinical manifestations of diabetic nephropathy in patients with diabetes type 1 and type 2.…”
Section: Discussionmentioning
confidence: 87%
“…Another hypothesis is that the greater use of calcium channel blockers by hypertensive patients with MetS could have resulted in BP control, but not in avoiding early renal damage, in agreement with several studies. 17 Another point to be mentioned is that despite of the greater use of antidiabetic drugs by patients with MetS, HbA1c remained higher in this group. On the other hand, studies 18 have consistently shown that levels of HbA1c < 7% are associated with a reduced risk of structural and clinical manifestations of diabetic nephropathy in patients with diabetes type 1 and type 2.…”
Section: Discussionmentioning
confidence: 87%
“…Because the present systematic review included a large number of RCTs, subgroup analysis, and modified statistical methods, it could provide stronger evidence than previous studies as well as previous meta-analyses[ 48 ]. The previous meta-analysis reviewed 530 citations and included 10 RCTs to derive the conclusion that RAAS blockade is superior to CCBs in terms of ESRD events but has a similar effect on mortality, as demonstrated by forest plots without subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Tidak ditemukan perbedaan bermakna pada kedua luaran klinis antara kelompok ARB dan CCB secara statistik. Hasil yang ditemukan pada penelitian didukung dengan hasil penelitian lain yang menyebutkan bahwa ARB dan CCB memiliki efek terapetik yang serupa untuk menurunkan tekanan darah pada pasien PGK (Lin et al, 2017;Zhao et al, 2016).…”
Section: Luaran Klinis Tekanan Darah Tak Terkontrol Dan Kejadian Kard...unclassified